A Leak in Paradise: Reputation Repair Policies After Offshore Data Leaks - Katarzyna Bilicka; Simone Traini (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
We examine whether the public revelation of sensitive tax information prompts firms to adopt reputation repair policies targeting shareholders. Between 2013 and 2021, the International Consortium of Investigative Journalists (ICIJ) released leaked information on over 800,000 offshore entities incorporated in tax havens, publicly revealing their use by multinational firms to avoid taxes. Leveraging this setting, we investigate whether firms implicated in the leaks improve their governance, increase investor remuneration, and reorganize their activities to restore shareholder trust relative to unaffected firms. We find that, after the leaks, firms appoint more directors, especially in operations, audit, and finance and accounting, pay higher dividends, and reduce their presence in tax havens, without increasing effective tax rates. Additional analyses suggest that concerns about managerial diversion and public scrutiny may drive these responses. Overall, data leaks appear to change the cost-benefit trade-off of tax strategies in ways that are, on net, favorable to shareholders.
Keywords: G30; H25; L14; M41; 330; offshore subsidiaries; tax havens; data leaks; corporate governance; dividend payouts; reputation repair